A 56-year-old woman with stress-induced hoarseness. (24th April 2012) - Latus, Joerg; Franke, Ulrich; Alscher, M Dominik; Braun, Niko
Abstract : A 56-year-old woman was admitted to hospital due to stress-dependent hoarseness and hypertensive urgency. The patient reported peaks of blood pressure of 210/160 mm Hg in combination with hoarseness. With indirect mirror examination, the ear-nose-and throat doctor diagnosed a paralysis of the vocal cord on the left side. The authors suspected a mass affecting the vagus nerve and performed a CT-scan with iodinated contrast material of the neck and thorax. Surprisingly the CT-scan showed an aneurysm of the aortic arch with a dilatation up to 4.8 cm, a kinking of 120° and a chronic dissection in the aneurysm. During exercise or elevated blood pressure this aneurysm expanded and made a compression of the nervus laryngeus recurrens on the left side. Thus, there is an explanation for the patient's hoarseness on exertion and during hypertensive urgency.